2005
DOI: 10.1073/pnas.0506289102
|View full text |Cite
|
Sign up to set email alerts
|

Tonic and acute nitric oxide signaling through soluble guanylate cyclase is mediated by nonheme nitric oxide, ATP, and GTP

Abstract: Nitric oxide (NO) affects many physiological systems by activating cGMP signaling cascades through soluble guanylate cyclase (sGC). In the accepted model, NO binds to the sGC heme, activating the enzyme. Here, we report that in the presence of physiological concentrations of ATP and GTP, NO dissociation from the sGC heme is Ϸ160 times slower than the rate of enzyme deactivation in vitro. Deactivated sGC still has NO bound to the heme, and full activation requires additional NO. We propose an activation model w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
169
4
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 138 publications
(183 citation statements)
references
References 42 publications
7
169
4
2
Order By: Relevance
“…When the activity was probed ϳ4 min after exposure to NO, the sGC-NO complex was only a few -fold more active than the resting sGC (Fig. 4), consistent with previous findings that stoichiometric NO does not lead to full activation of sGC (21,22,26). This low activity was not due to sGC protein aggregation during preincubation with NO.…”
supporting
confidence: 76%
See 4 more Smart Citations
“…When the activity was probed ϳ4 min after exposure to NO, the sGC-NO complex was only a few -fold more active than the resting sGC (Fig. 4), consistent with previous findings that stoichiometric NO does not lead to full activation of sGC (21,22,26). This low activity was not due to sGC protein aggregation during preincubation with NO.…”
supporting
confidence: 76%
“…S1). Previous reports demonstrated that sGC-NO complexes formed over several minutes with excess NO donor (21,26) or with stoichiometric NO donor in the presence of GTP (21,22) have the high cGMPforming activity expected from fully activated sGC. Our measurements corroborated these observations and demonstrated that high cGMP-forming activity was retained for up to 260 s after the sGC-NO complex was formed with excess NO gas or with stoichiometric NO in the presence of GTP (Fig.…”
mentioning
confidence: 99%
See 3 more Smart Citations